Elementary Teachers’ Knowledge on Fraction Multiplication: An Anthropological Theory of the Didactic Approach - Putra, Zetra Hainul (JOURNAL OF TEACHING AND LEARNING IN ELEMENTARY EDUCATION (JTLEE), 2019)
This study aims to evaluate Indonesian in-service elementary teachers’ knowledge on fraction by their responses to contextual problems on multiplication of a fraction by a whole number (O1) and multiplication of a fraction by a fraction (O2). Fifty Indonesian in-service elementary teachers from Elementary School for Teacher Education study program, University of Riau, participated in this research in 2015. This research is based on anthropologicaltheory of the didactic (ATD), in particular praxeology, as a framework to analysethe data. The result showed that only 22% of Indonesian in-service elementary teachers have a satisfactory relation to O1 and 64% of them have succeeded on the problems related to O2.